2022
DOI: 10.1021/acsanm.2c02426
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of Zn Single-Atom Catalysts on In2O3 Nanomaterials for Direct Synthesis of Acetic Acid from CH4 and CO2

Abstract: The direct conversion of methane and carbon dioxide will be a promising way to alleviate the greenhouse gas effect and reduce the dependency on traditional fossil fuels. In this study, the catalytic transformation of methane and carbon dioxide to acetic acid with a 100% atomic economy effect over the zinc single-atom catalyst supported on In2O3 nanomaterial with surface oxygen vacancy (Zn1/In2O3–x ) was investigated by using density functional theory calculations, including dissociative adsorption of methane, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“…For C 2 H 2 adsorption, the overlap of Rh 4d and C 2p orbitals results from the bond formation between C 2 H 2 and the active site. 29,48 In accordance with the results of adsorption energy, the supported Rh 4 site shows the most overlap among these three sites with the lowest adsorption energy. The total charge of activated C 2 H 2 on the supported Rh 4 site is −0.11 |e|, which indicates the strong electron transfer from the metal site to absorbate.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…For C 2 H 2 adsorption, the overlap of Rh 4d and C 2p orbitals results from the bond formation between C 2 H 2 and the active site. 29,48 In accordance with the results of adsorption energy, the supported Rh 4 site shows the most overlap among these three sites with the lowest adsorption energy. The total charge of activated C 2 H 2 on the supported Rh 4 site is −0.11 |e|, which indicates the strong electron transfer from the metal site to absorbate.…”
Section: Resultssupporting
confidence: 81%
“…7,[26][27][28] Furthermore, oxygen vacancies over indium oxide with the modification by single atoms show unique properties compared with pristine oxygen vacancies. For example, Zhou et al 29 suggested that the oxygen vacancy with a Zn single atom over the In 2 O 3 (111) facet is active for the synthesis of acetic acid from CH 4 and CO 2 . The presence of Zn single atoms not only facilitates the formation of Zn-CH 3 species but also regulates the properties of the oxygen vacancy.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the dissociation of CH 4 occurs on the Pd 10 cluster to create CH 3 * and H* with a barrier of only 0.81 eV. It is lower than the barriers reported in previous catalytic systems for the same reaction, such as Zn SAC (0.87 eV), Fe/ZnO (0.93 eV), CeO 2 -ZnO/MMT (0.97 eV), Au-ZSM-5 (1.41 eV), and sulfated zirconia (1.49 eV). ,, The difference between the two pathways begins at the C–C coupling step. In path A, CH 3 * couples directly with CO 2 * into CH 3 COO* with a barrier of 1.65 eV.…”
Section: Resultsmentioning
confidence: 82%
“…Yoshizawa et al explored the reaction mechanism for the direct conversion of methane to methanol on the surface of Pd as well as Pd/Au catalysts, and showed that the weakly bound hydroxyl groups on Au sites in the Pd/Au alloys contribute to the C–H bond cleavage process and are able to reduce the methane activation energy barrier (to 14.7 kcal/mol) . Besides, alloy catalysts such as single-atom alloys (SAA) and high-entropy alloys (HEA) can be tuned to achieve better catalytic performance by modulating the systematic size of the active sites. However, in disordered alloys, multiple types of adsorption sites can lead to the formation of local segregation, thus inhibiting catalyst confinement …”
Section: Introductionmentioning
confidence: 99%